Data preparation for relation model for transport and economy equlibrium - Salava, Daniel (Univerzita Pardubice, 2010)
This article is focused on statistical methodology for preparative phase of equilibrium model construction betwen systems by means of lation analysis and especially partial problems, that can occure by this analysis and obstruct solution relevance.
Keywords: relation model; transport figure; economical figure; equilibrium; correlation; variable; regression; indicator